The Marketing 4.0 Strategy for Laying Duck Farmers in Padangbulia Village - Ni Luh Nurkariani; Putu Yuma Siska Osela (Lembaga Riset dan Inovasi Al-Matani, 2025)
Over time, there have been several significant developments in the laying duck farming industry. Accessibility and the availability of raw materials are the main driving factors behind the growth of this sector. The aim of this research is to explore the various marketing strategies employed by laying duck farmers in Padangbulia Village. This study uses a qualitative methodology and falls under a phenomenological research approach. It aims to produce written or verbatim data from informants and observed behaviors. Both primary and secondary data sources were used. The research subjects were laying duck farmers. Data collection techniques included interviews and documentation. Data analysis involved data collection, reduction, presentation, and conclusion drawing/verification. No specific packaging methods were used. When egg prices increase, farmers are required to boost their production to meet customer demand, which may lead to a shortage of duck eggs.